Strategi Dinas Pariwisata, Kebudayaan, Kepemudaan dan Olahraga Kabupaten Sumedang dalam Upaya Mewujudkan Sumedang Sebagai Kabupaten Pariwisata - Silvia Wandanita Etin; Gilang Pratama Putra; Tedi Supriadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sumedang has been named a Tourism Regency by the Regent of Sumedang since 2019, but there are still many people who do not know about it. The purpose of this research is to find out how the strategy is applied in an effort to realize Sumedang as a Tourism Regency, what are the external and internal factors that influence it and how understanding is applied to the community regarding efforts to realize Sumedang as a Tourism Regency. This research uses a case study design involving several communities and the government, namely the Sumedang Regency Tourism, Culture, Youth and Sports Office. Data collection was conducted using semi-structured interviews with 14  participants. Data analysis to identify, create themes and evaluate inductively and thematically was carried out with the help of NVivo 12. Validation of instruments and data was carried out through triangulation and expert review techniques.  This research resulted in five findings: Disparbudpora strategy, the role of the media, Sumedang tourist destinations, challenges, and public understanding. The study concluded that the Strategy of the Department of Tourism, Culture, Youth and Sports focuses on a long-term plan that aims to optimize the achievement of all relevant objectives. This strategy includes monitoring and evaluating all activities related to tourism in the Sumedang Regency area, ensuring the development of infrastructure to support the development of tourism.